`Seeing' the state in India - Chandhoke, Neera (2005)
Since the early 1990s, civil society organisations have been involved with governments in an effort to `mobilise and organise the poor with a view to empowering them', converting them from `passive recipients of doles to active participants in planned development'. But what does this partnering of the state by civil society in crucial areas of collective life imply for the autonomy of the latter? And does the involvement of civil society mean that the state, instead of strengthening its own institutions for the delivery of basic services, has actually liberated itself from obligation to its citizens? A contrary view, however, emerges from a survey undertaken in a few residential areas of Delhi. Responses across the board indicated that citizens had high expectations from the state in spite of the fact that the state has begun to delegate more and more of its responsibilities to civil society organisations. As this article argues, such political preferences are the outcome of historical processes and how the development state came into being in post-independent India. - Reproduced.
Keywords: Economic planning - India; Economic planning